KARAKTERISTIK KEBUTUHAN RUANG PARKIR ANGKUTAN BARANG DI PT.SEMEN CIBINONG Tbk PABRIK CILACAP - NURUL HARIMANSYAH (Universitas Muhammadiyah Yogyakarta, 2004)
KARAKTERISTIK KEBUTUHAN RUANG PARKIR ANGKUTAN BARANG DI PT.SEMEN CIBINONG Tbk PABRIK CILACAP